2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347271
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extubation readiness in extreme preterm infants based on measures of cardiorespiratory variability

Abstract: The majority of extreme preterm infants require endotracheal intubation and mechanical ventilation (ETT-MV) during the first days of life to survive. Unfortunately this therapy is associated with adverse clinical outcomes and consequently, it is desirable to remove ETT-MV as quickly as possible. However, about 25% of extubated infants will fail and require re-intubation which is also associated with a 5-fold increase in mortality and a longer stay in the intensive care unit. Therefore, the ultimate goal is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Mikhno and Ennett used machine learning to classify whether or not there will be extubation failure during ventilation using 6 features (eg, heart rate) to predict the outcome. Precup et al used support vector machines to determine the combination of measures of cardiorespiratory variability, computed automatically, that best predicts extubation readiness. Their results suggest that the addition of their classification approach to current clinical measures may potentially reduce the extubation failure rate by more than 80%, where about 25% of extubated infants will fail and require reintubation.…”
Section: Introductionmentioning
confidence: 99%
“…Mikhno and Ennett used machine learning to classify whether or not there will be extubation failure during ventilation using 6 features (eg, heart rate) to predict the outcome. Precup et al used support vector machines to determine the combination of measures of cardiorespiratory variability, computed automatically, that best predicts extubation readiness. Their results suggest that the addition of their classification approach to current clinical measures may potentially reduce the extubation failure rate by more than 80%, where about 25% of extubated infants will fail and require reintubation.…”
Section: Introductionmentioning
confidence: 99%
“…This means that at the time infants were deemed ready for extubation, 8 out of 10 failures would be prevented, but at the expense of unnecessarily prolonging the course of mechanical ventilation in 5 out of 10 successes. Previous work [12] which applied SVM (on a much smaller cohort) using cardiorespiratory variables gave comparable sensitivity but a higher specificity of 74%. It will be necessary to repeat those experiments with this larger dataset.…”
Section: Discussionmentioning
confidence: 91%
“…high specificity), but not as sensitive in detecting failures. In [12], using patients of the same cohort, a Support Vector Machine (SVM) was developed to predict extubation readiness directly from the combination of cardiorespiratory variability measures. This system achieved improved ability to detect extubation failures (sensitivity of 83%) while maintaining a fairly high specificity of 74%.…”
Section: Related Workmentioning
confidence: 99%
“…Abbreviated cardiorespiratory studies (ACS) are commonly performed to assess/study respiratory conditions such as apnea, when full polysomnography (PSG) is not indicated or available (e.g., in the home [1], the recovery room [2], or the intensive care unit [3]). These studies acquire a subset of the PSG signals, typically including blood oxygen saturation (SaO 2 ) and photoplethysmography (PPG), measured with an oximeter, as well as the ribcage and abdomen respiratory movements from respiratory inductive plethysmography (RIP).…”
Section: Introductionmentioning
confidence: 99%